MANAJEMEN PEMBINAAN CLUB PRESTASI TENIS LAPANGAN PADA DEDDY TENIS CLUB KOTA PONTIANAK - Fadhilah Fatin; Isti Dwi Puspita Wati; Rubiyanto Rubiyanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
In an organization, there are needs to be managed to regulate how the continuity of an organization is. There is no exception for a club. In management, there are four main functions of management such as planning, organizing, implementation, and controlling. If the functions are running well, the club that implements management will get better results then. This research aimed to determine how the management coaching to the Deddy Tennis Club. The research type used in this research was descriptive qualitative using general interview methods and data triangulation. The data sources in this research were coaches, administrators, training children, and parents of athletes as data reinforcement. The result stated in this research indicated that the management applied to the Deddy Tennis Club was optimal. Because out of the four management functions, there is only one function less than optimal, namely the planning function. The planning function didn't run well because of the beginning of the club's establishment. The coach didn’t take many parts for the extension of the club in the future. Meanwhile, the other three functions as organizing, actuating, and controlling have been running well, even showing advantages.